The participation motive in the paralympics - Omar Fauzee, Mohd Sofian; Mohd Ali, Manisah; Soh, Kim Geok; Ibrahim, Norazillah (Guild of Independent Scholars, 2010)
The purpose of this case study is to examine the factors that influenced the participation of individuals with disability in sports. An interview was carried out on ten athletes with disability (female=3; male=7) who participated in the Malaysian Paralympics Sports Competition. All of the respondents have signed an inform consent letter to be tape recorded. Output of the interview was transcribed verbatim and content analysis was carried out to identify the common themes. The findings of the study found five factors that influence participation of individuals with disability in sports; fun, support, fitness, reward, and reduce stress. The finding also showed that despite the disability that they have, the motives of involving in sports were similar to those who have no known disability.